Regional Resources and Democratic Secessionism - Kai Gehring; Stephan A. Schneider (Center for Economic Studies and ifo Institute (CESifo), 2018)
Although regional resources have been shown to influence secessionist conflicts in developing countries, their effect in established democracies has largely been neglected. We integrate regional resource value and inter-regional transfers in a model on the optimal size of nations, and show that regional wealth correlates positively with secessionist party success in a large panel of regions. To establish causality, our difference-in-differences and triple-differences designs exploit that Scotland and Wales both feature separatist parties, but only an independent Scotland would profit from oil discoveries off its coast. We document an economically and statistically significant positive effect of regional resources and rule out plausible alternative explanations.
Keywords: D70; H77; N90; 330; fiscal federalism; inter-regional transfers; redistribution; secession; separatism; size of nations; resources; economic voting